Pengaruh Kinerja Laba (Earnings Per Share) dan Persepsi Pasar (Price Earnings Ratio) terhadap Nilai Perusahaan, dengan Tingkat Pengembalian Aset (Return on Assets) sebagai Variabel Moderasi. (Studi Empiris Perusahaan Subsektor Transportasi dan Logistik Yang Terdaftar di Bursa Efek Indonesia Periode 2020–2024) - Rof Boys Saroha Simamora; José António Bobo; Jercia do Carmo Ximenes (Jurnal Riset Multidisiplin Edukasi, 2026)
Firm value represents a key indicator reflecting corporate performance, future prospects, and market confidence, particularly in the transportation and logistics subsector characterized by high uncertainty and competition. This study aims to examine the effect of earnings performance, proxied by Earnings Per Share (EPS), and market perception, measured by the Price Earnings Ratio (PER), on firm value, with Return on Assets (ROA) as a moderating variable. Employing a quantitative causal research design, the study analyzes secondary data from 11 transportation and logistics firms listed on the Indonesia Stock Exchange over the 2020–2024 period. Data were collected from annual financial statements and analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that PER has a positive and significant effect on firm value, while EPS shows no significant effect. ROA does not moderate the EPS–firm value relationship but significantly moderates the effect of PER on firm value. These findings highlight the dominant role of market perception and asset efficiency in firm value creation and provide implications for managers and investors.